Evolution of the Polish political regime in the period of democratic transition - Glajcar, Rafał (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Transition, which is the starting point for any democratic change, in the Polish political context constituted a period of development of institutional solutions, which set the direction for the evolution of the political regime in sensu stricto in the years to come. An analysis of the relationship between the parliament, the president and the government requires that a reference be made to the traditional political regime models, that is parliamentarism, presidentialism and semi‑presidentialism. The functioning of either of these models assumes that a certain democratic minimum exists both in terms of a set of formal rules and political practice. Meanwhile, in the initial phase of the system change (from the Round Table to the first, fully competitive parliamentary elections in 1991), institutions characteristic for both democratic and authoritarian regimes functioned alongside each other. In these conditions, institutions restricted the political actors’ freedom of action by creating the political framework. The period of democratic transition perfectly illustrates the influence of actors on the shaping of specific institutional solutions. Key words: transition, political regime, parliament, president, government